School, supervision and adolescent-sensitive clinic care: combination social protection and reduced unprotected sex among HIV-positive adolescents in South Africa - Toska, E; Cluver, L; Boyes, M; Isaacsohn, M; Hodes, R; Sherr, L (Springer Verlag, 2016)
Social protection can reduce HIV-risk behavior in general adolescent populations, but evidence among HIV-positive adolescents is limited. This study quantitatively tests whether social protection is associated with reduced unprotected sex among 1060 ART-eligible adolescents from 53 government facilities in South Africa. Potential social protection included nine 'cash/cash-in-kind' and 'care' provisions. Analyses tested interactive/additive effects using logistic regressions and marginal effects models, controlling for covariates. 18 % of all HIV-positive adolescents and 28 % of girls reported unprotected sex. Lower rates of unprotected sex were associated with access to school (OR 0.52 95 % CI 0.33-0.82 p = 0.005), parental supervision (OR 0.54 95 % CI 0.33-0.90 p = 0.019), and adolescent-sensitive clinic care (OR 0.43 95 % CI 0.25-0.73 p = 0.002). Gender moderated the effect of adolescent-sensitive clinic care. Combination social protection had additive effects amongst girls: without any provisions 49 % reported unprotected sex; with 1-2 provisions 13-38 %; and with all provisions 9 %. Combination social protection has the potential to promote safer sex among HIV-positive adolescents, particularly girls.